Heaven and Earth Are Not Humane : the Problem of Evil in Classical Chinese Philosophy. - Perkins, Franklin (Bloomington, IN : Indiana University Press, 2014)
That bad things happen to good people was as true in early China as it is today. Franklin Perkins uses this observation as the thread by which to trace the effort by Chinese thinkers of the Warring States Period (c.475-221 BCE), a time of great conflict and division, to seek reconciliation between humankind and the world. Perkins provides rich new readings of classical Chinese texts and reflects on their significance for Western philosophical discourse.
Introduction: Philosophy in a Cross-Cultural Contex -- 1. Formations of the Problem of Evil -- 2. The Efficacy of Human Action and the Mohist Opposition to Fate -- 3. Efficacy and Following Nature in the Dàodéjing -- 4. Reproaching Heaven and Serving Heaven in the Mèngzï -- 5. Beyond the Human in the Zhuangzï -- 6. Xúnzï and the Fragility of the Human -- Conclusion.
Print version record.
Includes bibliographical references (pages 271-284) and index.
English.
JSTOR
Keywords: Philosophy, Chinese -- To 221 B.C.; Good and evil; Philosophy & Religion; Philosophy; Philosophie chinoise -- Jusqu'à 221 av. J.-C.; PHILOSOPHY -- Ethics & Moral Philosophy; PHILOSOPHY -- Social; PHILOSOPHY -- Good & Evil; Good and evil; Philosophy, Chinese; Das Böse; Philosophie; China; To 221 B.C.